Poverty, pollution, and mortality: The 1918 influenza pandemic in a developing German economy - Richard Franke (The Economic History Review, 2022)
The paper provides a detailed analysis of excess mortality during the 'Spanish Flu' in a developing German economy and the effect of poverty and air pollution on pandemic mortality. The empirical analysis is based on a difference-in-differences approach using annual all-cause mortality statistics at the parish level in the Kingdom of Württemberg. The paper complements the existing literature on urban pandemic severity with comprehensive evidence from mostly rural parishes. The results show that middle- and high-income parishes had a significantly lower increase in mortality rates than low-income parishes. Moreover, the mortality rate during the 1918 influenza pandemic was significantly higher in highly polluted parishes compared with least polluted parishes. Furthermore, the paper provides a detailed description of mortality statistics in Württemberg and new excess mortality rate estimates for Germany and its states.
Keywords: 330; air pollution; income; mortality; pandemics; Spanish Flu